The Influence of Islamic Value-Based Character Education on the Formation of Students’ Morals - Murtadlo, Sururul; Arifin, A Zaenal; Situmeang, Muhamad Sukri (STAI Publisistik Thawalib Jakarta, 2025)
Character education for early childhood is crucial for instilling moral, religious, and social values through habituation, exemplary behavior, play, and cultural integration to develop a positive personality from an early age. This study aims to assess the effectiveness of the IRCE model in systematically instilling Islamic values to shape morally upright and socially responsive young children. The research employed a quantitative correlational design, including validity and reliability tests and t-tests conducted using SmartPLS. The results indicate that the t-statistic for the IRCE–SM relationship is 24.406 with p = 0.000, far exceeding the critical t-value of 1.96, indicating a significant relationship. The very small p-value further confirms that this effect is not due to chance, demonstrating that changes in IRCE genuinely impact SM. In early childhood education, structured learning based on the teachings of the Qur’an and Hadith has been shown to foster positive attitudes. Children exhibit enthusiasm for learning, emulate Hadith teachings, adhere to rules, and demonstrate honesty, politeness, and empathy. They avoid negative behaviors, show discipline, and are helpful, resulting in the strong development of Islamic character. Conclusion: The IRCE model significantly influences character development in children, enhancing learning motivation, religious attitudes, empathy, discipline, and positive behavior through the teaching of Qur’anic and Hadith values.